Eliminating Trap‐States and Functionalizing Vacancies in 2D Semiconductors by Electrochemistry. Issue 47 (22nd October 2019) - Shi, Jianjian; Zhao, Xunhua; Wang, Zhiguo; Liu, Yuanyue
Abstract: One major challenge that limits the applications of 2D semiconductors is the detrimental electronic trap states caused by vacancies. Here using grand‐canonical density functional theory calculations, a novel approach is demonstrated that uses aqueous electrochemistry to eliminate the trap states of the vacancies in 2D transition metal dichalcogenides while leaving the perfect part of the material intact. The success of this electrochemical approach is based on the selectivity control by the electrode potential and the isovalence between oxygen and chalcogen. Motivated by these results, electrochemical conditions are further identified to functionalize the vacancies by incorporating various single metal atoms, which can bring in magnetism, tune carrier concentration/polarity, and/or activate single‐atom catalysis, enabling a wide range of potential applications. These approaches may be generalized to other 2D materials. The results open up a new avenue for improving the properties and extending the applications of 2D materials. Abstract : Chalcogen vacancies are harmful to the electronic and optoelectronic performance of 2D metal dichalcogenides due to the creation of trap states for electrons/holes. Here through first‐principles calculations, it is shown by using aqueous electrochemistry that chalcogen vacancies can be passivated and the trap states can be eliminated, suggesting an approach to improve the performance of 2D metal dichalcogenides.